2010
DOI: 10.1093/pubmed/fdq056
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol misuse, sexual risk behaviour and adverse sexual health outcomes: evidence from Britain's national probability sexual behaviour surveys

Abstract: In Britain, sexual risk behaviours and some adverse sexual health outcomes continue to be associated with excess alcohol consumption. These findings support addressing the link between alcohol misuse and sexual health in health services and through broader health promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 31 publications
1
35
1
1
Order By: Relevance
“…Numerous studies have shown associations between smoking, cervical cancer and HPV infection 22. We have previously shown that those who have more partners are likely to smoke and drink more alcohol 23 24. In our study, the association between smoking and HPV infection no longer remained significant in multivariate analysis suggesting confounding of the association by sexual behaviour.…”
Section: Discussioncontrasting
confidence: 49%
“…Numerous studies have shown associations between smoking, cervical cancer and HPV infection 22. We have previously shown that those who have more partners are likely to smoke and drink more alcohol 23 24. In our study, the association between smoking and HPV infection no longer remained significant in multivariate analysis suggesting confounding of the association by sexual behaviour.…”
Section: Discussioncontrasting
confidence: 49%
“…Muitos fatores podem ser explicados em consequência das mulheres terem mais acesso ao mercado de trabalho e à escolaridade, logo novas configurações e possibilidades nas relações familiares, sexuais e sociais ocorreram 22 . Em concordância com outros estudos 13,14,21,23 , a prevalência desses comportamentos de risco tende a ser maior entre os grupos de menor renda, entretanto, o gap diminuiu na última década, especialmente para a iniciação sexual. Em geral, comportamentos sexuais de risco e alguns eventos adversos em saúde sexual estão associados com o consumo de álcool.…”
Section: Discussionunclassified
“…Research has highlighted stimulants, especially cocaine [Edlin et al, 1994; Mathers et al, 2008] and methamphetamine [Colfax, 2004; Shoptaw & Reback, 2006], as a driver of sexual risk behavior. There is increasing evidence that alcohol, through disinhibition, may exert a similar effect on sexual risk [Castilla, Barrio, Belza and de la Fuente, 1999; Aicken, Nardone and Mercer, 2011; Van Tieu and Koblin, 2009]. In contrast, opiates, as potential inhibitors of libido and sexual function [Lejuez et al, 2005], have not been found to be consistent predictors of sexual risk behavior.…”
mentioning
confidence: 99%